1993
DOI: 10.1063/1.108901
|View full text |Cite
|
Sign up to set email alerts
|

Insitu growth of epitaxial YBa2Cu3O7 thin films by on-axis unbalanced direct current magnetron sputtering

Abstract: Superconducting YBa2Cu3O7−x thin films are prepared in situ by on-axis dc magnetron sputtering from a single stoichiometric target. The magnetron uses an unbalanced magnetic field configuration to eliminate resputtering effects, and high quality thin films on MgO (100) substrates are realized with excellent reproducibility. The target is sputtered in Ar/O2 mixture at a fixed partial pressure ratio pAr/pO2= 15:1. We report on the growth and properties of films deposited (a) as a function of the total sputtering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Most of the YBCO films were grown on 10 × 10 mm 2 MgO substrates by dc magnetron sputtering from a sintered target of stoichiometric YBCO, followed by in situ annealing in oxygen [14]. The YBCO films used in the in situ contact samples were deposited via thermal co-evaporation by Theva GMBH.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the YBCO films were grown on 10 × 10 mm 2 MgO substrates by dc magnetron sputtering from a sintered target of stoichiometric YBCO, followed by in situ annealing in oxygen [14]. The YBCO films used in the in situ contact samples were deposited via thermal co-evaporation by Theva GMBH.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 ␥-Mo 2 N is known as a superconductor with T c ϳ 5 K. 3 We reported that ␤-Mo 2 N is also a superconductor with T c ϳ 5 K. 4 It was reported that the hexagonal ␦-MoN was crystallized in a slightly distorted NiAs type structure under 6 GPa, 5,6 and the resulting phase showed superconductivity with T c ϳ 12 K. 3,5 A theoretical study predicted that MoN with the cubic NaCl type structure ͑so called B1-MoN͒ would have T c as high as 29 K. [7][8][9][10] Since B1-MoN is believed to be a metastable phase, many studies adopted thin film deposition techniques, such as magnetron sputter, ion-beam assisted deposition, and ion implanting for the synthesis of the phase. [11][12][13][14][15][16][17] The B1-MoN films reported in the literature, however, have not exhibited such "high T c ." Later, theoretical studies predicted the elastic instability of the B1-MoN cubic structure, and suggested that orthorhombic, tetragonal or trigonal distortions would be more preferable.…”
mentioning
confidence: 99%
“…Due to the high superconducting transition temperature and hardness, good thermal and electronic conductivity, as well as chemical stability, molybdenum nitrides, in particular molybdenum mononitrides, have caused particular interest both theoretically and experimentally 1–23. Experimentally, bulk molybdenum nitride was known to exist only in hexagonal forms.…”
Section: Introductionmentioning
confidence: 99%
“…176) 3. Besides the bulk materials, high‐ T c superconductor MoN film in NaCl structure was also synthesized by dc‐magnetron sputtering 10, reactive magnetron sputtering 11, and low‐energy ion‐assisted deposition 12.…”
Section: Introductionmentioning
confidence: 99%